2013
DOI: 10.1007/s00586-013-3116-7
|View full text |Cite
|
Sign up to set email alerts
|

Spinal canal morphology and clinical outcomes of microsurgical bilateral decompression via a unilateral approach for lumbar spinal canal stenosis

Abstract: Microsurgical bilateral decompression via a unilateral approach may be a good modality for treating round or oval shape spinal canal stenosis, but is not recommended for trefoil-shaped-stenosis. The current authors recommend performing the bilateral decompression technique in cases of trefoil-shaped-spinal canal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…Based on the outcome results, they concluded that bilateral decompression via a unilateral approach may be a good modality for treating round or oval shape spinal canal stenosis, but they did not recommended it for trefoilshaped stenosis [43].…”
Section: Discussion Backgroundmentioning
confidence: 99%
“…Based on the outcome results, they concluded that bilateral decompression via a unilateral approach may be a good modality for treating round or oval shape spinal canal stenosis, but they did not recommended it for trefoilshaped stenosis [43].…”
Section: Discussion Backgroundmentioning
confidence: 99%
“…55 Stenosis may take place centrally at the central canal or laterally at the lateral recess, or the neural foramina. 8 Interplay of variable factors comprehensive of loss of height and herniation of intervertebral disc, facet joint thickening and hypertrophy of ligamentum flavum is the main pathophysiology leading up to reduced spinal canal diameter with subsequent compression of neural elements. 14,29,33 Compressioninduced ischemia of cauda equina and nerve roots provoke symptoms related to LCS which encompass neurogenic claudication described as buttock/ radiating leg pain with or without low back pain that get worsened with prolonged standing or walking and relieved with sitting or forward-leaning.…”
Section: Discussionmentioning
confidence: 99%
“…8 Johnsson et al, 23 1992 conducted a study upon LCS patients who were managed conservatively and followed-up for almost 4 consecutive years. Only 15% of the patients show symptomatic improvement with equal percentages get worsened.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, more work needs to be done in defining the adequate role of tubular minimally invasive laminectomies in patients with lumbar stenosis given radiological parameters other than spondylolisthesis, such as facet joint anatomy, disc height, foraminal compression, and spinal canal morphology. 2 We are currently studying the quality of contralateral versus ipsilateral decompression via a unilateral approach.…”
mentioning
confidence: 99%
“…Many of these procedures are now being performed via minimally invasive techniques. 2,4,5 The evolution of minimally invasive spine surgery has touched all aspects of lumbar spine pathology. Application of this technology has influenced the treatment of lumbar tumors, trauma, and deformity.…”
mentioning
confidence: 99%